Answer :

Answer:X = 2

Step-by-step explanation:

Apply the distributive property.

2x+2⋅5+4(x−9)=−142x+2⋅5+4(x-9)=-14

Multiply 22 by 55.

2x+10+4(x−9)=−142x+10+4(x-9)=-14

Apply the distributive property.

2x+10+4x+4⋅−9=−142x+10+4x+4⋅-9=-14

Multiply 44 by −9-9.

2x+10+4x−36=−142x+10+4x-36=-14

Simplify by adding terms.

6x−26=−146x-26=-14

Move all terms not containing xx to the right side of the equation.

Add 2626 to both sides of the equation.

6x=−14+266x=-14+26

Add −14-14 and 2626.

6x=126x=12

Divide each term by 66 and simplify.

Divide each term in 6x=126x=12 by 66.

6x6=1266x6=126

Cancel the common factor of 66.

x=126x=126

Divide 1212 by 66.

x=2

Other Questions